PENGARUH MODEL SURVEY, QUESTION, READ, RECITE, RECORD, REVIEW (SQ4R) BERBANTUAN MEDIA EDUCANDY UNTUK MENINGKATKAN KEMAMPUAN PENGUASAAN KOSAKATA BAHASA INGGRIS PESERTA DIDIK SEKOLAH DASAR - Nurmahanani, Indah; Fajrussalam, Hisny; Robin, Shavega Julia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
There are four main skills that learners must master when they want to master English, namely, listening, speaking, reading, and writing. These skills are influenced by how much vocabulary the learners master. This study is to test whether there is a relationship between reading and improving vocabulary mastery so that the SQ4R model is chosen. The research problem is to find out and analyze the improvement and influence of the SQ4R model assisted by Educandy media compared to students who get the TTW learning model. The method in this study uses quasi experiments non-equivalent pre-test post-test ontrol group with road safety material with a sample size of 50 students. There are instruments that are used to obtain data before and after students are given treatment or treatment. This study concluded that, there is an increase in mastery of English vocabulary and the effect on the effect of using the SQ4R learning model assisted by Educandy media is better than students who use the TTW model.